Atrial Electromechanical Coupling in Patients with Lichen Planus - Yaman, Mehmet; Arslan, Ugur; Beton, Osman; Asarcikli, Lale Dinc; Aksakal, Aytekin; Dogdu, Orhan (Korean Soc Cardiology, 2016)
Background and objectives: A chronic inflammatory disease, lichen planus may cause disturbance of atrial electromechanical coupling and increase the risk of atrial fibrillation. The aim of this study was to evaluate atrial electromechanical delay with both electrocardiography (ECG) and echocardiography in patients with lichen planus (LP). Subjects and Methods: Seventy-two LP patients (43 males [59.7%], mean age: 44.0 +/- 16.7 years) were enrolled in this cross-sectional case-control study. The control group was selected in a 1: 1 ratio from 70 patients in an age and sex matched manner. P wave dispersion was measured by ECG to show atrial electromechanical delay. All of the patients underwent transthoracic echocardiography for measuring inter-and intra-atrial electromechanical delays. Results: The baseline characteristics of the patients and the control group were similar except for the presence of LP. P-wave dispersion measured by ECG was significantly higher in patients with LP (p<0.001). Patients with LP had significantly prolonged intra- and interatrial electromechanical delays when compared to the control group (p<0.001). In addition, all of these variables were significantly correlated with high sensitive C-reactive protein (hsCRP) levels. Conclusion: Atrial electromechanical coupling, which is significantly correlated with increased hsCRP levels, is impaired in patients with LP.
Keywords: Lichen planus; Echocardiography; Electrocardiography